Climbing anchors field guide - Long, John, 1953- (How to climb series., 2014)
"Explains how to create safe, simple, and efficient rock climbing anchoring systems. This pocketsize handbook shows how to properly place and configure natural anchors, passive chocks, mechanical chocks, fixed gear, knots, belay anchors, toprope anchors, and rappel anchors"--